Identification and Partial Characterization of a Dynamin-Like Protein, EhDLP1, from the Protist Parasite Entamoeba histolytica - Jain, Ruchi (American Society for Microbiology (ASM), 2010)
The dynamin superfamily of proteins includes a large repertoire of evolutionarily conserved GTPases that interact with different subcellular organelle membranes in eukaryotes. Dynamins are thought to participate in a number of cellular processes involving membrane remodeling and scission. Dynamin-like proteins (DLPs) form a subfamily of this vast class and play important roles in cellular processes, such as mitochondrial fission, cytokinesis, and endocytosis. In the present study, a gene encoding a dynamin-like protein (EhDLP1) from the protist parasite Entamoeba histolytica was identified and the protein was partially characterized using a combination of in silico, biochemical, and imaging methods. The protein was capable of GTP binding and hydrolysis, lipid binding, and oligomerization. Immunofluorescence studies showed the protein to be associated with the nuclear membrane. A mutant of EhDLP1 lacking GTP binding and hydrolyzing activities did not associate with the nuclear membrane. The results suggest a nucleus-associated function for EhDLP1.